Dipeptide-modified nanoparticles to facilitate oral docetaxel delivery: new insights into PepT1-mediated targeting strategy. (1st January 2018) - Du, Yuqian; Tian, Chutong; Wang, Menglin; Huang, Di; Wei, Wei; Liu, Yan; Li, Lin; Sun, Bingjun; Kou, Longfa; Kan, Qiming; Liu, Kexin; Luo, Cong; et al.
Abstract: Oligopeptide transporter 1 (PepT1) has been a striking prodrug-designing target. However, the underlying mechanism of PepT1 as a target to facilitate the oral absorption of nanoparticles (NPs) remains unclear. Herein, we modify Poly (lactic-co-glycolic acid) (PLGA) NPs with the conjugates of dipeptides (L-valine-valine, L-valine-phenylalanine) and polyoxyethylene (PEG Mw: 1000, 2000) stearate to facilitate oral delivery of docetaxel (DTX) to investigate the oral absorption mechanism and regulatory effects on PepT1 of the dipeptide-modified NPs. The cellular uptake of the dipeptide-modified NPs is more efficient than that of the unmodified NPs in the stably transfected hPepT1- Hela cells and Caco-2 cells, suggesting the involvement of PepT1 in the endocytosis of NPs. The internalization of the dipeptide-modified NPs is proved to be a proton-dependent process. Moreover, the L-valine-valine modified NPs with shorter PEG chain exhibit distinct advantages in terms of intestinal permeability and oral absorption, resulting in significantly improved oral bioavailability of DTX. In summary, PepT1 could serve as a desirable target for oral nanoparticulate drug delivery and the dipeptide-modified NPs represent a promising nanoplatform to facilitate oral delivery of hydrophobic drugs with low bioavailability.